(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Il contributo, accettato dal Direttore, riproduce il testo aggiornato della Relazione presentata al Convegno sul tema Transizioni e democrazia nei paesi del Mediterraneo e del vicino Oriente (Università della Calabria, 10-11 aprile 2013), in via di pubblicazione nei relativi Atti. SOMMARIO: 1. Premessa. Un paradigma per la “libertà religiosa mediterranea” – 2. La libertà religiosa come “prima libertà” – 2.1. La sponda nord – 2.2. La sponda sud – 3. La libertà religiosa nell’età contemporanea: apogeo e declino? – 4. Libertà religiosa e pluralismo musulmano in Europa – 5. Libertà religiosa e pluralismo musulmano in terra d’islam – 6. Alcune osservazioni conclusive. Where religious freedom is heading: common paths on both sides of the Mediterranean ABSTRACT The paper aims to investigate the path of religious freedom on the two sides of the Mediterranean. Assuming the possibility of a synoptic history, the paper observes this synopsis from three different perspectives: historical, political and pluralistic. Taking the Declaration of Universal Human Rights as a common parameter for the two sides, the paper analyzes the contemporary process of politicization of the right of religious freedom both in Europe and in the MENA countries. Stressing the fact that the core of this right has to be individuated into the autonomy from the state of both (religious) individuals and communities, the paper advocates a defense of religious freedom as an autonomous and specific right, not completely merged with the generic protection of freedom of conscience and with the goals of the states. This kind of conflation, in fact, could subvert the fundamental distinction between religious and civil spheres, with harmful consequences for both the state and religious communities.